Grafting in Brinjal (Solanum melongena L.) for Growth, Yield and Quality Attributes - Kumar, B. Ashok; Pandey, A. K.; Raja, P.; Singh, Siddhartha; Wangchu, L. (International Journal of Bio-resource and Stress Management, 2017)
The effect of different rootstocks on eggplant growth, fruit yield, and fruit quality were studied by comparing grafted plants with non-grafted ones under low cost polyhouse. The present investigation was carried out in the year, 2014–15, Experimental Farm, Department of Vegetable Science, College of Horticulture and Forestry (CAU) Pasighat. The experiment was laid out in Completely Randomised Design with 8 treatments (four wild Solanum species and two eggplant genotypes) and four replications. The seedlings of eggplant genotypes with pencil thickness were grafted with wild Solanum species by cleft method. The non-grafted plants were used as control. The highest survival rate observed in plants grafted with Solanum torvum followed by Solanum surathense. The plant morphology, reproductive and yield parameters were significantly affected by grafting. Control plants recorded minimum plant height with least number of leaves per plant. Furthermore, fruit weight, fruit yield, days to fruit maturity and rooting behaviour of plant were influenced positively by grafting. All grafted plants showed superior rooting and highest number, length, fresh weight and dry weight of roots were recorded in Solanum torvum followed by solanum khasianum. Based on mean performance, grafted plants of Solanum torvum and Solanum khasianum found to be superior for plant growth and yield attributing characters without effecting fruit quality. So, it can be concluded that grafting in eggplant is quite successful and alternate method of production.